Task-Irrelevant Auditory Feedback Facilitates Motor Performance in Musicians - Conde, Virginia; Altenmüller, Eckart; Villringer, Arno; Ragert, Patrick (Frontiers in Psychology, 2012)
An efficient and fast auditory–motor network is a basic resource for trained musicians due to the importance of motor anticipation of sound production in musical performance. When playing an instrument, motor performance always goes along with the production of sounds and the integration between both modalities plays an essential role in the course of musical training. The aim of the present study was to investigate the role of task-irrelevant auditory feedback during motor performance in musicians using a serial reaction time task (SRTT). Our hypothesis was that musicians, due to their extensive auditory–motor practice routine during musical training, have a superior performance and learning capabilities when receiving auditory feedback during SRTT relative to musicians performing the SRTT without any auditory feedback. Here we provide novel evidence that task-irrelevant auditory feedback is capable to reinforce SRTT performance but not learning, a finding that might provide further insight into auditory-motor integration in musicians on a behavioral level.